Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 13 - Section 13.1 - The Indefinite Integral - Exercises - Page 958: 4



Work Step by Step

$\displaystyle \int(-5)dx=\quad$...Constant MultipIe Rule =$(-5)\displaystyle \int 1\cdot dx$=$(-5)\displaystyle \int x^{0}dx$ ...Power Rule $,n=0\neq-1$ $=(-5)\displaystyle \frac{x^{0+1}}{0+1}+C$ $=-5x+C$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.